Perspective towards End-of-Life Care among Nurses Working in BPKIHS: A Cross-Sectional Study - Parajuli, Shalu; Phuyal, Sharishma; Shrestha, Erina; Mehta, Ram Sharan (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: End-of-life care (EOLC) is the term used to describe the support and medical care given to dying patients and their families during the time surrounding death. It has a direct impact on the attitude of nurses towards the care of dying. We aimed to assess the perspective towards end-of-life care and its association with different socio-demographic variables among the nurses working in B.P. Koirala Institute of Health Sciences (BPKIHS).Methods:  This cross-sectional study was carried out among 136 nurses working in the selected settings of BPKIHS. Simple random sampling was used to select staff nurses and purposive sampling to select senior staff nurses and senior Auxiliary Nurse Midwifes. Frommelt Attitude towards Care of the Dying (FATCOD-B) scale was used to assess the nurses' perspective towards care of dying. Data were analyzed using SPSS version 17.0. Descriptive statistics were used for describing sample characteristics. The Chi-square test was used to show the association between level of attitude and socio-demographic variables.Results: Almost two-third (64%) of the nurses had a fair attitude, 36% had a good attitude. The socio-demographic characteristics i.e.; marital status, ward/unit, level of education, designation, total duration of work, experience of caring for dying, and training on end-of-life care were significantly associated with the nurses' attitude towards care of dying.Conclusion: Overall, nurses had a fair attitude towards the care of dying; none had a poor attitude.